Langstaff : A Nineteenth-Century Medical Life - Duffin, Jacalyn (Book collections on Project MUSE., 1993)
A unique and readable microhistory of an ordinary physician and his community during a period of revolutionary medical change. Duffin bases her insights on a detailed computer-assisted analysis of 40 years of extant daybooks of James Langstaff (1825-1889).